Research on Wireless Relay Application in TD-LTE Network - Jiangbo Dong; Wei Liu; Yunbo Han; Hao Sun; Yanlei Chen; Nan Li (Dianxin kexue)
Wireless relay can solve the problems of covering blind spots，which was caused by lack of cable transmission，difficult at station site property coordination of macro base station，high-rise block. By two means of actual field test and network simulation，the coverage performance of relay was assessed comprehensively at outdoor coverage and indoor blind spots. By analyzing the distance between relay and buildings，the relationship between relay deployed position height and the interior depth coverage，relay deployment recommendations were given for solving depth coverage gaps.